Software development of welding procedure specification for flux cored arc welding / Huzaymi Zamri. - Zamri, Huzaymi (2006)
The development of Welding Procedure Specification (WPS) using computer programming was given in order to overcome the inefficiency made by traditional means. The project involves preparation of WPS format and acquisition of data. Theoretically, it's a continuation of previous work in GTAW, GMAW, SMAW, Spot Welding and SAW. All the welding processes and data from previous works had been restructured and the job was to continue with Flux Cored Arc Welding (FCAW). The welding software was developed using Visual Basic 6.0 programming Language with Structured Query Language (SQL) so that welding parameters can be obtained quickly while the programming of data are in action. To make it as a user friendly and flexible, the software has been developed based on Microsoft Operation System Platform.This software will display at lease the basic parameters required in FCAW welding processes in form screen. The user only needs to key in the variables for the relevant welding processes and the welding parameter will be automatically displayed. This software is suitable to be used by skillful and qualified welder and those personnel involved in welding activities such as welding engineers and so on. Once the parameters are accepted or have been qualified they may be used, saved, updated, deleted, retrieved or printed out in the form mode. The flexibility on making this WPS will makes life easy and welding preparation will become more efficient.